ANALISIS PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA PROSES PEMBELAJARAN MATEMATIKA DI KELAS V SD NEGERI - Bimby Haly Irrawan; Wahyudi Wahyudi; Ngatman Ngatman (Universitas Sebelas Maret, 2022)
AbstractThis study aims to describe the use of information and communication technology in learning mathematics in class V SD Negeri 2 Kebumen. This study uses a qualitative research method with a case study approach. The results of this study are as follows. First, the use of information and communication technology in mathematics learning has been carried out well, the process of using information and communication technology focuses on the use of whatsapp groups as a medium for delivering material in online learning. Second, there are several advantages of using information and communication technology in learning mathematics in the era of the covid-19 pandemic. Third, in learning mathematics using information and communication technology during the COVID-19 pandemic, there are several obstacles that need to be considered by teachers, principals, students, and guardians of fifth grade students at SD Negeri 2 Kebumen during the learning process. The conclusion obtained from the results of this study is that the use of information and communication technology in learning mathematics in class V SD Negeri 2 Kebumen has been implemented properly using online media such as whatsapp groups which have advantages and have obstacles and efforts have been made to handle it by all parties. Keywords: use of information and communication technology, online learning AbstrakPenelitian ini bertujuan untuk mendeskripsikan penggunaan teknologi informasi dan komunikasi pada pembelajaran matematika di kelas V SD Negeri 2 Kebumen. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Hasil penelitian ini yaitu sebagai berikut. Pertama, penggunaan teknologi informasi dan komunikasi pada pembelajaran matematika sudah terlaksana dengan baik, proses penggunaan teknologi informasi dan komunikasi berfokus pada penggunaan whatsapp grup sebagai media penyampaian materi pada pembelajaran daring. Kedua, terdapat beberapa faktor kelebihan penggunaan teknologi informasi dan komunikasi pada pembelajaran matematika di era pandemi covid-19. Ketiga, pada pembelajaran matematika menggunakan teknologi informasi dan komunikasi selama masa pandemi covid-19 terdapat beberapa kendala yang perlu di perhatikan oleh guru, kepala sekolah, siswa, dan wali siswa kelas V SD Negeri 2 Kebumen selama proses pembelajaran. Kesimpulan yang diperoleh dari hasil penelitian tersebut yaitu penggunaan teknologi informasi dan komunikasi pada pembelajaran matematika di kelas V SD Negeri 2 Kebumen sudah terlakasana dengan baik menggunakan media online seperti whatsapp grup yang memiliki kelebihan serta memiliki kendala dan telah dilakukan upaya penanganan oleh semua pihak. Kata Kunci: penggunaan teknologi informasi dan komunikasi, pembelajaran daring